2020
DOI: 10.1155/2020/2436191
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic Characteristics of Encased Differential Gear Train with Journal Bearing

Abstract: Taking the marine encased differential gear train as an example, the relationship between the journal bearing parameters and the meshing force of the transmission system is analyzed. In this paper, the dynamic model of the encased differential gear train with journal bearing is established considering the factors of time-varying meshing stiffness and comprehensive transmission error. In this dynamic model, four stiffnesses and four damping coefficients are applied to characterize the asymmetry and interaction … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 22 publications
(26 reference statements)
0
3
0
Order By: Relevance
“…When a high-speed train runs at high speed for a long time, the gearbox bearing is prone to cracks and deformation. Additionally, the wheelset of the running gear system will be squeezed and worn when it touches the ground for a long time, and this will be corroded by different environments while staying at a high-temperature status [35]. e air spring also has the possibility of gas leakage, and the stiffness degradation of the shock absorber steel spring can occur.…”
Section: Problem Descriptionmentioning
confidence: 99%
“…When a high-speed train runs at high speed for a long time, the gearbox bearing is prone to cracks and deformation. Additionally, the wheelset of the running gear system will be squeezed and worn when it touches the ground for a long time, and this will be corroded by different environments while staying at a high-temperature status [35]. e air spring also has the possibility of gas leakage, and the stiffness degradation of the shock absorber steel spring can occur.…”
Section: Problem Descriptionmentioning
confidence: 99%
“…The trajectory of the gear shaft supported by the journal bearings can have significantly larger orbits (depending on the hydrodynamic clearance) and stronger coupled stiffness compared with roller bearings [10]. The findings from [11] and [12] for the case of a marine propulsion gearbox showed that the journal bearings influenced the gear meshing forces. There are only a few publications available regarding the influence on the gear forces of a wind turbine gearbox when roller bearings are replaced with journal bearings.…”
Section: Introductionmentioning
confidence: 99%
“…Zhang et al [6][7][8] studied the dynamic characteristic of a coaxial contrarotating encased differential gear train. Yang et al [9] investigated the dynamic characteristic of an encased differential gear train with journal bearing. Despite the considerable research conducted by scholars on the dynamic characteristics of encased differential planetary gear systems, there remains a lack of in-depth investigation into the floating support structures and their load-sharing characteristics.…”
Section: Introductionmentioning
confidence: 99%